Face-Tracking Mount Display for Medical and Engineering Applications - Jecu, Silviu Alin; Demeter, Andreea Georgiana; Bogdan, Ioana Corina (IEEE, 2023)
This paper presents a face-tracking mount display (FTMD) that, has applications, such as medicine (telerobotics surgery), home automation or research and development of integrated circuits by positioning the display to assure the best viewing angle. The working principle of the FTMD is designed to recognize and identify the relative position and number of persons that are watching the display. Through the Kanade-Lucas-Tomasi (KLT) and Haar Cascade (HC) algorithms and synchronized actuators, the FTMD can change its orientation and inclination angles, ensuring the best-average view. The large number of medical devices that are using cameras in the non-invasive surgery or endoscopy is rising. The output of such devices is a sort of video that can be projected on the display. A FTMD would facilitate the viewing angles for the medical personnel as they move during operations. Further, this device can be implemented on the “Vision Cart”, which is part of the DaVinci Robot, transmitting the video output from the “Surgeon Console” and “Patient Cart” to the display. The DaVinci Robot is a great example of medical improvement. This system has as its main points the patient cart, surgeon console, and vision cart. The FTMD mode of operation is based on computer vision, where the camera detects how many people are in a room and, based on the KLT and HC algorithm, moves himself according to it.